Biomass production and chemical composition of essential oil of Piper callosum as affected by spacing in Manaus, Amazonas State, Brazil - Chaves, F. C M; Batista, A. C.; Mendonça, M. B.; DeHidalgo, A. F.; Ming, Lin Chau [UNESP]; Bizzo, H. R.; Souza, A. M.; Pinto, M. A S (My University, 2011)
The family Piperaceae contains nearly 2000 species, most of them distributed in two genera, Piper and Peperomia. In Brazil circa 170 Piper species are found, mainly in tropical areas Their use ranges from flavoring and culinary to raw material for pharmaceutical and cosmetic industry. One of these species, Piper callosum, is used in folk medicine in the Amazon area. The objective of this study was to evaluate the production of biomass (aerial parts) as well as yield and composition of the essential oil from the leaves, according to different spacing between cultivated plants at Embrapa Western Amazon, in Manaus, State of Amazonas, Brazil. The experimental design was randomized blocks, with four treatments and seven replicates with six plants. Biomass production was inversely proportional to the spatial arrangements, with the greatest biomass production (1034.93 kg/ha) in the shortest spacing (E1), although no statistical difference was verified between E3 and E4. The same response was observed for the production of essential oil. The chemical composition of the oil was not affected by spacing, and major compounds found were safrole (59.1%), beta-pinene (8.3%), alpha-pinene (6.5%), methyl eugenol (6.3%) and 1,8-cineole (4.1).
Keywords: Amazon; Essential oils; Medicinal plants; Piper callosum; Piperaceae; Safrole; Peperomia